Molecularly Designed Zinc (II) Phthalocyanine Derivative as Dopant‐Free Hole‐Transporting Material of Planar Perovskite Solar Cell with Preferential Face‐on Orientation. Issue 11 (17th June 2019) - Hu, Qikun; Rezaee, Ehsan; Dong, Lei; Dong, Qingshun; Shan, Haiquan; Chen, Qian; Li, Minzhang; Cai, Siyuan; Wang, Liduo; Xu, Zong-Xiang
Abstract : Efficient and stable hole‐transporting materials (HTMs) are necessary for perovskite solar cells (PSCs) with excellent efficiency and long‐term stability. Here, two A3 B‐type metal phthalocyanine (MPc) compounds are prepared as dopant‐free HTMs for conventional n‐i‐p structured PSCs. Mono‐ n ‐butyl‐substituted zinc phthalocyanine and hexamethyl‐mono‐n‐butyl‐substituted zinc phthalocyanine (Me6 Bu‐ZnPc) are synthesized through ring‐expansion method, and their exact structures are characterized using nuclear magnetic resonance and mass spectroscopy. The molecular orientation of the developed HTM thin films against the underlying surface is studied using X‐ray diffraction. Different substituents in MPcs can strongly affect their molecular orientation, resulting in different hole mobilities. The favored face‐on molecular alignment is only observed for Me6 Bu‐ZnPc on the perovskite layer, proving the crucial role of methyl substituents in controlling the molecular alignment through the special interactions between the MPc molecule and different sites of perovskite material on the surface. PSCs using Me6 Bu‐ZnPc as a dopant‐free HTM yields the highest reported power‐conversion efficiency (PCE) of 17.41%. With its high hydrophobicity and good coverage, Me6 Bu‐ZnPc HTM thin film acts as an encapsulation layer, which leads to significantly increased long‐term stability. The Me6 Bu‐ZnPc‐based devices retain over 90% of their initial PCE after 1400 h storage at 25 °C and with a relative humidity of 75%. Abstract : Hexamethyl‐mono‐ n ‐butyl‐substituted zinc phthalocyanine (Me6 Bu‐ZnPc) is synthesized through a ring‐expansion method. The favored face‐on molecular alignment is observed for Me6 Bu‐ZnPc on the perovskite layer. Perovskite solar cells using Me6 Bu‐ZnPc as the dopant‐free hole‐transporting material achieve the highest power‐conversion efficiency (PCE) of 17.41% and retain over 90% of their initial PCE after 1400 h storage at 25 °C and with a relative humidity of 75%.